University Strategy in an Age of Uncertainty: the Effect of HIgher Education Funding on Old and New Universities - Hizer, Rolf (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
University Strategy in an Age of Uncertainty: the Effect of HIgher Education Funding on Old and New Universities // Higher Education Quarterly, Vol. 57. No. 1, January 2003, pp 24–47. Translated from the English by N. Dergunova